Effect of cooling rates and Zr addition on the microstructure and corrosion behaviors of the Mg–Zn–Gd alloys. (4th January 2018) - Zhang, Jinyang; Jia, Peng; Xu, Shumin; Lou, Gui; Zhou, Guorong; Zhao, Degang; Teng, Xinying
Abstract: The grain size of Mg96 Zn1 Gd3 alloys was refined by increasing cooling rate and adding Zr refiner. At the cooling rate of 122.8 K s −1, the primary dendrite spacing decreased from 12.5 to 6.4 μ m with the Zr addition in Mg96 Zn1 Gd3 alloy casting into a copper mold. At the 0.3 K s −1, the long-period stacking ordered structure phase (LPSO) only was formed in Mg96 Zn1 Gd3 alloy casting into a sand mold. The research concerned on mechanical properties showed that hardness of Mg95.8 Zn1 Gd3 Zr0.2 alloy was increased from 82.7 to 121.1 HBW with the increase of the cooling rate. About the high temperature performance, the melt temperature of the second phase was 882 K, and it was not changed with the Zr addition and the change of cooling rates. However, the excellent corrosion resistance corresponded to the large grain size was changed by the formation of the LPSO phase in Mg96 Zn1 Gd3 alloy.